Renal Tubular Permeability during Increased Intrarenal Pressure - Lorentz, William B. (1972)
Renal tubular permeability was studied by microinjection techniques during increased intrarenal pressure in anesthetized diuretic rats. Intrarenal pressure, as evidenced by intratubular pressure (ITP), was increased by elevation of ureteral pressure, partial renal venous constriction, or massive saline diuresis. Various combinations of radioactive inulin, creatinine, mannitol, sucrose, and iothalamate in isotonic saline were microinjected into superficial proximal and distal convolutions, and recovery of the isotopes was measured in the urine. Inulin was completely recovered in the urine from the injected kidney at both normal and elevated ITP. Creatinine, mannitol, sucrose, and iothalamate were also completely recovered at normal ITP, but recoveries were significantly lower, averaging 73, 85, 89, and 85%, respectively, after early proximal injection when proximal ITP was increased to 30±2 mm Hg by elevation of ureteral pressure. Since transit time is prolonged under these conditions, mannitol recovery was also studied during aortic constriction, which prolongs transit time but lowers ITP. Recovery was complete. A significant loss of mannitol was observed during massive saline diuresis, which shortens transit time but increases ITP. During renal venous constriction producing a proximal ITP of 30±2 mm Hg, mannitol recovery was significantly less than 100% even after microinjection into distal convolutions, but the loss was greater injection at more proximal puncture sites. Mannitol recovery was complete during elevation of ureteral pressure in the contralateral kidney. These studies demonstrate a change in the permeability characteristics of all major segments of the renal tubule during elevation of intrarenal pressure. This change is rapidly reversible and does not appear to be due to a humoral factor which gains access to the general circulation.